Lovesick Ellie. 4 - Fujimomo (Kodansha USA Publishing, LLC, 2022)
"#PinkNewWorld. As Ellie gets to know the bratty boy behind handsome Ohmi's smooth-spoken facade, she falls harder and harder for him. In spite of misunderstandings during Sports Day, the two reconcile and confirm each other's feelings in the end. Ellie relishes in the fact that she gets to keep Ohmi to herself and fellow classmates are talking to her more -- including cheeky and aloof Kaname. Meanwhile, tensions grow awkward between Sara and her childhood friend, Reo, and hidden feelings begin to surface..."--Page [4] of cover.